The Theory of Relativity and Theology: The Neo-Thomist Science–Theology Separation vs. Michael Heller’s Path to Dialogue - Polak, Paweł (Theology and science, 2023)
Attempts to establish a dialogue between the natural sciences and theology were made in the 20th century along with, among other things, the arrival of new groundbreaking theories in physics, but these attempts met with many content-related and methodological challenges. Philosophy, which plays an essential role as an intermediary in this relationship, has often proven to be a significant obstacle. The failure of neo-Thomism’s reception to Einstein’s theory in Poland led the Polish cosmologist, philosopher, and theologian Michael Heller to introduce the concept of philosophy in science as a possible basis for dialogue. It proved fruitful, and years later, Heller was awarded the Templeton Prize for building bridges between science and theology. As it later transpired, the notion of philosophy in science has considerable intellectual potential for enriching the dialogue between natural sciences and theology. This article briefly discusses some examples of how the theory of relativity was received by some Polish neo-Thomists. Furthermore, the paper presents the sources of inspiration for Heller’s approach and the benefits it offers. Finally, another project that he named the theology of science is also discussed.